2008
DOI: 10.1038/cdd.2008.184
|View full text |Cite
|
Sign up to set email alerts
|

IEX-1 targets mitochondrial F1Fo-ATPase inhibitor for degradation

Abstract: IEX-1 (Immediate Early response gene X-1) is a stress-inducible gene. It suppresses production of reactive oxygen species (ROS) and protects cells from apoptosis induced by a wide range of stimuli, but the underlying mechanism is not known. This study reveals that IEX-1 targets the mitochondrial F1Fo-ATPase Inhibitor (IF1) for degradation, resulting in acceleration of ATP hydrolysis, concomitant with reduction in ROS production. A prominent role for IF1 degradation in the function of IEX-1 was corroborated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 39 publications
3
71
1
Order By: Relevance
“…1C), the protein will inhibit both the synthetic and hydrolytic activities. In agreement with our proposal, recent findings indicate that deletion of IEX-1, a stress-inducible gene that apparently targets IF1 for degradation, results in the inhibition of the ATP synthase activity in vivo (29).…”
Section: Discussionsupporting
confidence: 80%
“…1C), the protein will inhibit both the synthetic and hydrolytic activities. In agreement with our proposal, recent findings indicate that deletion of IEX-1, a stress-inducible gene that apparently targets IF1 for degradation, results in the inhibition of the ATP synthase activity in vivo (29).…”
Section: Discussionsupporting
confidence: 80%
“…15 Our previous investigation showed that mice lacking immediate early responsive gene X-1 (IEX-1) were more susceptible to secondary brain injury than their wild-type littermates, because the null mutation of IEX-1 adversely affected mitochondrial functions and therefore diminished ATP formation in the injured brain. 16,17 Interestingly, noninvasive LLL illumination robustly enhanced ATP generation in injured brains of IEX-1 knockout mice. The enhancement was correlated positively and proportionally with LLL-mediated protection against secondary brain injury in the mice, suggesting a key role for mitochondria in both the pathogenesis of secondary brain injury and the effectiveness of LLL.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…The immediate early responsive gene X-1 (IEX-1) has a pivotal role in regulation of mitochondrial F 1 F 0 -ATPase activity, in protection against apoptosis, and in resolution of inflammation. [13][14][15] Null mutation of IEX-1 enhanced apoptosis, 16 reduced ATP synthase activity, 17 and prolonged inflammatory responses in a tissue-dependent manner in mice. 15,18 Furthermore, IEX-1 is upregulated by NF-kB and in turn inhibits NF-kB activation as a negative feedback mechanism contributing to inflammation resolution.…”
Section: Traumatic Brain Injury (Tbi) Represents a Serious Public Healthmentioning
confidence: 99%